2022
DOI: 10.3389/fendo.2022.961471
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric and visualization analysis of glucocorticoid-induced osteoporosis research from 2012 to 2021

Abstract: IntroductionGlucocorticoid-induced osteoporosis (GIOP) is the most common cause of secondary osteoporosis. Although many studies related to GIOP have been published, there was no bibliometric analysis in this field. This study aimed to investigate the research trends on GIOP by using bibliometric analysis.Materials and MethodsAll data were collected from the Web of Science Core Collection (WoSCC). All original research articles regarding GIOP from 2012 to 2021 were retrieved. CiteSpace was used to analyze the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…This global trend is corroborated by various bibliometric studies related to osteoporosis, all demonstrating a similar pattern with different research leaders. [22–26]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This global trend is corroborated by various bibliometric studies related to osteoporosis, all demonstrating a similar pattern with different research leaders. [22–26]…”
Section: Discussionmentioning
confidence: 99%
“…This global trend is corroborated by various bibliometric studies related to osteoporosis, all demonstrating a similar pattern with different research leaders. [22][23][24][25][26] On the other hand, when adjusting the number of publications throughout the years of study, it was identified that on average only 5 countries had 5 or more publications per year.…”
Section: Annual Publicationsmentioning
confidence: 99%
“…The 2022 ACR guideline for the prevention and treatment of GIO describes sequential treatments recommended when the initial osteoporosis therapy and glucocorticoid therapy are discontinued depending on the fracture risk [ 75 ]. Further studies are needed to evaluate the utility of new diagnostic tools [ 76 , 77 ] and to conduct direct comparisons between the efficacies of GIO therapies [ 78 ].
Fig.
…”
Section: Perspectives and Recommendationsmentioning
confidence: 99%
“…It enables readers to obtain information about research hotspots and developing trends in a certain knowledge field (Zhu et al, 2022). In recent years, bibliometrics has been widely used in medical fields such as cancer, osteoporosis, depression, and cognitive impairment (Cai et al, 2022; Chen et al, 2022; Jiang et al, 2022b; Xiao et al, 2022). In addition, in the field of CVD, Liang et al, 2022 used bibliometrics to explore the trending use of reactive oxygen species-based nanotechnology for the diagnosis and treatment of CVD.…”
Section: Introductionmentioning
confidence: 99%